(3ScQOGf GdSWGfs - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3eMeO Hf CMeO Hf Ydi GdeDPf GdTGaYi GdeTQai s)
(3ChdgG (B:s
(3MjkG abGd dWQaI (B: (3GaJM cJGHc aeG ajg EdGeKd eG ajg ai cJGHi , abGd (B: (3Ef cGf GLJQC Ydjc , ade jcf djLJQF Ydi s
(3BNQgG (B:s
(3hbO JfGgi ai GdYdi eaQOG aGYLH ZOG eaQOG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B13 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B6 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B230 s
Keywords: (3GdJGQjNs